THE DEVELOPMENT OF THE OPERATION MODEL OF BUDDHIST ORIENTED SCHOOL - Suvichano (Buabarn), Phramaha Wicharn (Journal of MCU Nakhondhat, 2021)
The objectives of this article were: 1) to study the current state. Buddhist way of school operation mode. And 2) to develop a Buddhist method school operating model. By being a research on the development model by Conducting research, including 1) studying the conceptual framework of the research from document analysis, 2) studying conditions and problems using questionnaires Select a specific sample represented by an executive director from 379 persons, 3) studying the model and sketch of the pattern using semi - structured interviews. Select a specific sample represented by the Buddhist method school from 21 persons. To bring to draft the form by the workshop and check the draft by using expert seminar, and 4) to develop a Buddhist method school operating model by focus group. The sample was chosen by purposive sampling from 10 persons using the statistics, percentage, frequency ( ) mean and standard deviation (S.D.). By analyzing the content and summarizing. The research was found that: 1) the current state is the current Buddhist way schools operate at 3 levels such as: 1.1) the general Buddhist way schools, 1.2) the leading Buddhist school, and 1.3) the Buddhist ways of the royal school. There are 6 steps to implement such as: 1) Preparation, 2) Implementation of the condition and composition, 3) Implementation of the Trisikha system, 4) Close supervision, 5) Improvement and further development, and 6) Evaluation and dissemination of performance. And 2) the develop model by bringing the principles to support. There are 6 steps: 2.1) Belief and agency, 2.2) Panya Wuthitham, 2.3) Trisikha, 2.4) Kanlayanamit, 2.5) Ittibah 4 Upanyatham 2, and 2.6) Joy and appreciation together. And operating model at 3 levels such as: 1) a network of Buddhist ways of schools, 2) Building a Buddhist youth leader, and 3) community development based on the Buddhist way of life. To promote the process of operating the Buddhist schools to be more efficient.